Beyond the Similarity Score: A Phenomenological Case Study of Faculty Perspectives on Turnitin Plagiarism Detection Software at Landmark University, Nigeria - Kayode, Adeniy Isaiah; Tella, Adeyinka; Bashorun, Musediq Tunji; Akande, Samson Oyeniyi; Eromosele, George Osas; Oguntayo, Sunday Adebisi; Mark, Oragwa; Sani, Yusuf Muhammad (Inkunabula: Journal of Library Science and Islamic Information, 2026)
This study investigated faculty awareness, perceptions, and lived experiences with Turnitin plagiarism detection software at Landmark University, Nigeria. It aimed to assess understanding of the tool, evaluate its perceived role in promoting academic integrity, explore practical use in teaching and research, and identify associated benefits and challenges. A phenomenological approach was employed. Data were collected through structured online interviews with 25 faculty members (heads of department) purposively selected for their active use of Turnitin plagiarism detection software. Narrative analysis was used to identify key themes from the transcribed responses. Findings revealed a gap between operational awareness and pedagogical understanding of Turnitin. Faculty perceived a tension between its value as a formative educational tool and its institutional deployment as a summative, punitive mechanism. Lived experiences highlighted its role in standardising output and providing objective evidence, but also cited significant procedural burden and interpretive challenges. Key benefits included safeguarding institutional credibility and empowering faculty, while major challenges involved infrastructure, contextual interpretation of reports, and the emerging threat of generative AI. The study concludes that while Turnitin is successfully institutionalised as a compliance mechanism at Landmark University, its potential as a catalyst for a deeper academic integrity culture remains under-realised. To bridge this gap, a strategic shift from a policy-focused to a pedagogy-centered implementation is required. This involves investing in advanced faculty training, reframing institutional messaging, ensuring reliable infrastructure, and proactively developing strategies to address AI-assisted plagiarism. The study contributes theoretically by validating the integrated examination of awareness, perception, and lived experience as inseparable determinants of technology adoption in non-Western academic contexts, and practically by providing an evidence-based framework for transitioning from compliance-oriented to pedagogy-centered integrity infrastructure in Global South universities.